Faktor Risiko Kejadian Tuberkulosis di Puskesmas Landono Kabupaten Konawe Selatan - Amzal Mortin Andas; I Wayan Romantika; Ida Bagus Gede Antara Manuaba (Jurnal Keperawatan, 2019)
Tuberculosis has become one of the health problems that health workers have never completed. Various risk factors that increase the incidence of tuberculosis and must be controlled to reduce the incidence of tuberculosis. The purpose of this study was to analyze the risk factors for TB incidence. This type of research is analytic descriptive with a case-control design. The population in this study were all tuberculosis sufferers in the work area of ​​the Landono Health Center in the South Konawe Regency, in the 2018 period for 64 people. The sample was divided into two, 32 case samples (TB sufferers) and 32 control samples (no TB sufferers). The statistical test used was Chi-Square followed by Odds Ratio. The results showed the development and spread of tuberculosis in residential neighborhoods with a house humidity of ˃70%, ventilation area of ​​˂10% and residential density of ˂10 m2 per person are risk factors for Tuberculosis. Conclusion, house humidity, house ventilation area, and house occupancy density are risk factors for Tuberculosis. Suggestions, in the process of building a house all elements of the community must pay attention to aspects of house humidity, ventilation area, and residential density.